Obligation of negotiation and facultative arbitration as part of constitutional law content on collective negotiation - Boza Pró, Guillermo (2013)
This work studies constitutional bases of two essential institutions of Collective Labor Law: employer’s obligation to negotiate collectively and facultative arbitration. In relation to the first one, using tools provided bythe Theory of Law, it is argued that the section 28º of Peruvian Constitution establishes a collective negotiation concept as claim (not as permission) so, employers legal obligation of collective negotiation is constitutional. In theother hand, regarding facultative arbitration, it has constitutional support on state’s obligation to promote pacific ways to labor conflicts; even though, it is questioned that a «sub constitutional» rule has restrictively regulated this institution.